2010
DOI: 10.1002/cncr.25194
|View full text |Cite
|
Sign up to set email alerts
|

A validated prognostic index predicting response to dexamethasone and diethylstilbestrol in castrate‐resistant prostate cancer

Abstract: The easy-to-use prognostic index that the authors developed was able to identify a subgroup of patients with CRPC who had prolonged survival only 1 month after starting DS therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…CTCs may be useful in future to help decide which patients should stop this therapy early as their changes were much more rapid than PSA. This supports our previous work in which we developed an easy to use prognostic index to identify those individuals with a prolonged survival within 1 month of starting therapy using PSA (21), however in this case the use of intensive chemotherapy followed by reintroduction of hormonal treatment made early changes in PSA much less useful. The principle of early identification of response to a therapy is of particular importance in managing CRPC-in which the number of options has expanded, allowing a change to an alternative and minimizing toxicity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CTCs may be useful in future to help decide which patients should stop this therapy early as their changes were much more rapid than PSA. This supports our previous work in which we developed an easy to use prognostic index to identify those individuals with a prolonged survival within 1 month of starting therapy using PSA (21), however in this case the use of intensive chemotherapy followed by reintroduction of hormonal treatment made early changes in PSA much less useful. The principle of early identification of response to a therapy is of particular importance in managing CRPC-in which the number of options has expanded, allowing a change to an alternative and minimizing toxicity.…”
Section: Discussionsupporting
confidence: 85%
“…Following our recent data, we also wished to specifically observe whether changes in biomarkers (PSA or CTCs) at 1 month could predict survival (21). We found that responses in patients with heavily pretreated CRPC could be induced by our protocol, and that in those individuals with increased CTCs at the start of therapy, a rapid clincancerres.aacrjournals.org Downloaded from decrease was associated with a survival benefit.…”
Section: Discussionmentioning
confidence: 86%
“…Notably, the Gleason grade was highly predictive of the TDP under LH-RH analogs but not so of the TDP under DES therapy, suggesting important differences in the anticancer mechanism of action of both agents. In the study of Shamash et al (19), a PSA decrease >50% within 1 month of treatment with DES and corticosteroids was found to predict a favourable prognosis with median TDP greater than 1 year and median survival greater than 2 years.…”
Section: Discussionmentioning
confidence: 96%
“…More recently a study performed by Clemons et al [8] showed PSA response in 39% of patients with median TTP of 30 weeks (95% CI, 21.9-68.7). An interesting study conducted by Shamash et al [9] found that the level of PSA response 1 month after DES induction might serve as a surrogate marker for prediction of prolonged response to treatment. They constructed a prognostic index and demonstrated in 145 individuals with CRPC that only two factors were significant in predicting which patients will maintain a prolonged response to DES therapy.…”
Section: Discussionmentioning
confidence: 99%